Seven ideas that shook the universe - Spielberg, Nathan. (John Wiley and Sons, 1995)
This book is divided into nine parts: Introduction; Copernican Astronomy; Newtonian Mechanics and Causality; The Energy Concept; Entropy and Probability; Electromagnetism and Reality; Quantum Theory and the End of Causality; Conservation Principles and Symmetries; and Epilogue.